1995
DOI: 10.1016/s0741-5214(95)70274-1
|View full text |Cite
|
Sign up to set email alerts
|

Compromised cerebral blood flow reactivity is a predictor of stroke in patients with symptomatic carotid artery occlusive disease

Abstract: The loss of cerebral reactivity in patients with symptoms who had greater than or equal to 70% carotid stenosis or occlusion is an important predictor of impending cerebral infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
122
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(125 citation statements)
references
References 16 publications
1
122
0
2
Order By: Relevance
“…The mechanism for this, the CVR, secures the delivery of oxygen to the parenchyma of the brain. Recently it was shown that a diminished CVR is a predictor of stroke in patients with symptomatic carotid artery occlusive disease (16). Furthermore, cerebral periventricular white matter lesions have been found to be correlated with decreased vasomotor reactivity in asymptomatic individuals (17), increased stroke risk (18), first-ever lacunar infarction (19), and deep white matter lesions (20).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for this, the CVR, secures the delivery of oxygen to the parenchyma of the brain. Recently it was shown that a diminished CVR is a predictor of stroke in patients with symptomatic carotid artery occlusive disease (16). Furthermore, cerebral periventricular white matter lesions have been found to be correlated with decreased vasomotor reactivity in asymptomatic individuals (17), increased stroke risk (18), first-ever lacunar infarction (19), and deep white matter lesions (20).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of CVR has been used to evaluate cerebral vascular function over a broad range of clinical applications including to monitor the severity of brain damage after an ischemic event (Dohmen et al 2007), to predict the risk of a cerebral ischemic event in patients with carotid occlusive disease (Diehl 2002;Kleiser and Widder 1992;Markus and Cullinane 2001;Vernieri et al 1999, Webster et al 1995Yonas et al 1993), to assess the efficacy of a carotid endarterectomy (Herzig et al 2004), and to study anxiety disorders (Giardino et al 2007;Mathew and Wilson 1997) and migraine attacks (Akin and Bilensoy 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Steal phenomenon is a risk factor for future ischemic stroke. 1,2 In patients with Moyamoya disease, a progressive narrowing of the supraclinoid internal carotid artery (ICA) and its proximal branches, negative or severely reduced CVR has been used to identify patients who may benefit from surgical revascularization. 3,4 However, the impact of steal phenomenon on normal-appearing brain tissue (ie, in the absence of overt infarction) has not been previously investigated.…”
mentioning
confidence: 99%